2012
DOI: 10.1088/0004-637x/754/2/136
|View full text |Cite
|
Sign up to set email alerts
|

TRANSIT AND ECLIPSE ANALYSES OF THE EXOPLANET HD 149026b USING BLISS MAPPING

Abstract: The dayside of HD 149026b is near the edge of detectability by the Spitzer Space Telescope. We report on eleven secondary-eclipse events at 3.6, 4.5, 3 × 5.8, 4 × 8.0, and 2 × 16 µm plus three primary-transit events at 8.0 µm. The eclipse depths from jointly-fit models at each wavelength are 0.040 ± 0.003% at 3.6 µm, 0.034 ± 0.006% at 4.5 µm, 0.044 ± 0.010% at 5.8 µm, 0.052 ± 0.006% at 8.0 µm, and 0.085 ± 0.032% at 16 µm. Multiple observations at the longer wavelengths improved eclipse-depth signal-to-noise ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
276
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(290 citation statements)
references
References 62 publications
14
276
0
Order By: Relevance
“…The third, optional, function was a polynomial of the logarithm of time + a slope to represent a sharp decrease of the detector response at the start of the AOR ("ramp" effect, Knutson et al 2008). To improve the quality of the modelling of the pixel phase effect, especially the fitting of its highest frequency components, we supplemented the x-and y-polynomial with the Bi-Linearly-Interpolated Sub-pixel Sensitivity (BLISS) mapping method (Stevenson et al 2012). The sampling of the positions in space was selected so that at least five measurements fall within the same subpixel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third, optional, function was a polynomial of the logarithm of time + a slope to represent a sharp decrease of the detector response at the start of the AOR ("ramp" effect, Knutson et al 2008). To improve the quality of the modelling of the pixel phase effect, especially the fitting of its highest frequency components, we supplemented the x-and y-polynomial with the Bi-Linearly-Interpolated Sub-pixel Sensitivity (BLISS) mapping method (Stevenson et al 2012). The sampling of the positions in space was selected so that at least five measurements fall within the same subpixel.…”
Section: Discussionmentioning
confidence: 99%
“…Spitzer photometry divided by two different best-fit baseline models. The first (top) aims to remove position-and PSF effects, and consists of a 4th order polynomial of the PSF x-and y-centres and widths, supplemented with the BLISS mapping method (Stevenson et al 2012) to remove high-frequency position effects. The second baseline model (bottom) adds to the first a slope and a quadratic function of the logarithm of time to model the sharp decrease in the counts at the beginning of the run (negative ramp).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we use a modified implementation of the BLISS (BiLinearly-Interpolated Subpixel Sensitivity) method (Stevenson et al 2012).…”
Section: Intra-pixel Sensitivity Correctionmentioning
confidence: 99%
“…For an improved modelling of the effect, Ballard et al (2010a) and Stevenson et al (2012a) demonstrated the efficiency of building a "pixel map" to characterise the intra-pixel variability on a fine grid. Here we combine the bi-linearly-interpolated sub-pixel sensitivity (BLISS) mapping method presented by Stevenson et al (2012a) with the position/FWHM polynomial models. The BLISS mapping is performed at every step of the chain after the modelling of the polynomial models.…”
Section: The Intra-pixel Sensitivity and Pixelation Modellingmentioning
confidence: 99%